Transnational Solidarity - Not Aid: The Perspective of Migration on the Hype about Migration&Development - Schwertl, Maria (Social Inclusion, 2017)
Migrants have organized transnational support for non-migrants, stay-at-homes, citizens and noncitizens, as well as for developmental or integrationist nation state projects for decades. These solidarities have been framed as "cultural programs," "autochthone support of hometowns," "development aid" or "diaspora politics." Since the turn of the century especially those projects that could be framed as "development aid" have gained a lot of interest from official development aid and its agencies. More and more programs have been launched to coordinate and professionalize the transnational support labor of migrants under the aegis of development. This is what I call the hype about migration&development. In this article, I want to show why the notion of "migrant development aid" used in the hype falls short of what is at stake when it comes to transnational migrant solidarities. Thereby, I want to argue that looking at migration through its governance and through migration or development politics is short-sighted and insensitive towards the desires, ethics and politics of migration. This is the reason that a perspective of migration—such as that propagated by the autonomy of migration approach—needs to be brought into debates on migration&development.